TRANSANAL ENDOSCOPIC MICROSURGERY FOR RECTAL TUMORS : A SYSTEMATIC REVIEW - Ade Ansari, Witia; Sri Putri Handayani; Febriana, Dita; Utami, Deviani; Wirawan, Ahmad (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2024)
Background: Tumors of the rectal region are common. Originally, transanal endoscopic microsurgery (TEM) was intended as a substitute therapy for these lesions. Methods: By comparing itself to the standards set by the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020, this study was able to show that it met all of the requirements. So, the experts were able to make sure that the study was as up-to-date as it was possible to be. For this search approach, publications that came out between 2014 and 2023 were taken into account. Several different online reference sources, like Pubmed and SagePub, were used to do this. It was decided not to take into account review pieces, works that had already been published, or works that were only half done. Result: In the PubMed database, the results of our search brought up 832 articles, whereas the results of our search on SagePub brought up 75 articles. The results of the search conducted for the last year of 2014 yielded a total 7 articles for PubMed and 9 articles for SagePub. In the end, we compiled a total of 5 papers, 4 of which came from PubMed and 1 of which came from SagePub. We included five research that met the criteria. Conclusion: In summary, TEM has proven to be a dynamic technology and essential platform in treating diseases of different disciplines, despite its initial introduction 38 years ago. We assume that its primal indication of small benign adenomas was comparatively mature yet the application of TEM could be expanded to larger ones, its application in rectal cancer could be more flexible and early-stage cancer should not limit the popularization of TEM in large medical institutions, especially in selected patients after neoadjuvant chemoradiotherapy.